(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Listihani L, Yuniti IGAD, Sapanca PLY, Pandawani NP, Selangga DGW. 2023. The antiviral potential of macroalgae in suppressing Sweet potato leaf curl virus (SPLCV) infection in sweet potatoes. Biodiversitas 24: 4079-4086. Sweet potato leaf curl virus (SPLCV) was first found in sweet potatoes in Indonesia in 2022. Prevention of spread of virus is essential, especially by using macroalgae extract which is environmentally friendly and has antiviral activity. The aim of present research was to test the potential of sea macroalgae to suppress SPLCV infection and to analyze phytochemicals of potential macroalgae containing an antiviral substance. Macroalgae extract was sprayed on the test plants that were infected by SPLCV. The observed parameters were changes in symptoms, disease incidence and severity, virus confirmation by PCR, and phytochemical analysis. The test results up to day 21 showed that Eucheuma spinosum was found to be effective in suppressing SPLCV infection in sweet potatoes, up to symptomless infection in young leaves. E. spinosum and E. cottonii suppressed disease incidence by 80% and 40% and lower disease severity as much as 71% and 48%, while E. serra showed less ability to suppress SPLCV infection. The two macroalgae had flavonoid, saponin, and steroid content which may be the reason to suppress the viral infection. The results of PCR analysis showed that microalgal extract had the highest nucleotide and amino acid homology with Gianyar (LC586170) isolate with values of 99.7 and 100%. The macroalgae with the highest ability to suppress the virus were E. spinosum and E. cottonii. This showed that the application of macroalgae extract did not change the amino acid sequence of SPLCV isolate.